Atom probe tomography analysis of Nb3Sn superconducting wires for fusion reactor and particle accelerator applications - Wheatley, L (2023)
First discovered in 1954, Nb3Sn is a low temperature superconductor, which has had a resurgence in interest in recent years. Multiple projects, such as the Hi-Lumi upgrade to the Large Hadron Collider and the fusion reactor ITER have used Nb3Sn superconducting magnets, and there are plans to use improved Nb3Sn wires for a Future Circular Collider (FCC). Nb3Sn is the second most commercially available superconductor after NbTi, which revolutionised the medical sector making MRI machines possible. However, NbTi has a maximum field of 14 T, compared to the higher maximum field of 28 T for Nb3Sn. The FCC target is 1500 Amm-2 at 16 T, much more challenging than previous applications of Nb3Sn. To reach this target fluxons, which are 3 - 4 nm in radius in Nb3Sn, need to be trapped at defects within the Nb3Sn microstructure. Historically, grain refinement has been the main method of increasing the Jc by maximising the grain boundary area which can pin fluxons. Commercial Nb3Sn wires have a grain size of ≈ 100 nm, however, it is difficult to reduce the grain size further and still produce a homogeneous Nb3Sn layer with favourable superconducting properties. To increase Jc to reach the FCC target, artificial pinning centres (APCs), on the scale of the fluxons are required. Considering the importance of the nanoscale structure on the superconducting properties of Nb3Sn, little is known about nanoscale chemical segregation within Nb3Sn. In this work, Atom Probe Tomography (APT) has been used to understand the nanoscale structure of two different types of Nb3Sn wires, restacked-rod-processed (RRP®) and rod-in-tube (RIT) type wires. The first set of results focuses on a commercial RRP® wire doped with Ti and a comparative RRP® wire, irradiated at a neutron fluence of 2.82 x 1022m-2 in the TRIGA II reactor. The inter-grain compositions, intra-grain compositions and any additional features such as dislocations were studied. Both RRP® samples had intra-grain compositions which were formed of two different, non-equilibrium compositions, one higher in Nb and one lower in Nb. The irradiated RRP® sample had a lower volume of high Nb compared to the as-received sample, this suggests that irradiation induced diffusion has occurred due to the excess of vacancies produced during neutron irradiation. The second set of results focuses on a RIT test wire which reached the high Jc requirement for the FCC. The pinning curve from this wire suggested the presence of APCs, despite no intentional source of oxygen added to the wire, to produce APCs through internal oxidation. An Electron probe micro-analyser (EPMA) and APT have been used to determine the oxygen concentration in the unreacted and reacted Nb-4Ta-1Hf (at%) alloy, with evidence of HfO2 nanoparticles in the reacted Nb-4Ta-1Hf alloy. In a similar way to the RRP® samples, the intra-grain and inter-grain compositions of the Nb3Sn layer have been measured, and the size and number density of HfO2 APCs have been calculated. Additional features have been analysed, such as a residual Nb6Sn5 layer at the edge of the Nb3Sn region and residual Cu rich phases trapped within the Nb3Sn layer. Evidence of HfO2 in the reacted Nb-4Ta-1Hf alloy and the Nb6Sn5 layer shows HfO2 nanoparticles were formed prior to Nb3Sn and that the HfO2 nanoparticles may have acted as Zener pinning sites to reduce the grain size of the Nb3Sn. Nb6Sn5 has been shown to have a higher Cu solubility than Nb3Sn, perhaps explaining the trapped regions of Cu rich phases within the Nb3Sn. For future Nb3Sn applications it is important to understand the effect of neutron irradiation and the presence of APCs on the nanoscale chemical segregation in Nb3Sn wires in order to design Nb3Sn with better superconducting properties. This work has shown that APT is a useful technique to analyse the nanostructure of Nb3Sn wires.